Explaining the Modern Transformation of Islamic Legal Contracts: Theoretical and Practical Implications - (:unkn) unknown (BRILL, 2020)
This article both examines changing contexts and factors that cause transformation as well as shows their effects on Islamic finance contracts. Here the author addresses his general theories in terms of modern igtihad (independent reasoning) on modern Islamic finance contracts. The main question is: 'How have changing contexts and factors affected the emergence and transformation of Islamic financial contracts?' The study addresses contexts, factors, and conditions that severely transform contracts. More specifically, the author argues that modern Islamic finance contracts have been transformed by the effects of changing factors and contexts. The main objective is to uncover modern contractual developments in Islamic finance and show how this transformation has made its mark on modern Islamic finance contracts. The study consists of a presentation of historical background, an explanation of socio-economic and ideological-ethical contexts and factors creating change, and a discussion regarding their effects on modern Islamic contracts.
Keywords: contracts; legal change; Islamic finance; Islamic banking; Islamic law